Smart Aquaculture Controlling System - M S Asren, Ahmad Faruq (IRC, 2019)
In this modern era, the technology of Internet of Things (IoT) is growing quickly. There are so many IoT implementation in several industries including aquaculture industries. As for traditional fish farmers, they have the difficulties in controlling the quality of water such as water temperature, water pH level etc. It gives a bad impact for the fish farmers to produce a good product and slowly will harm the aquaculture industry. By creating a system using IoT in this industry, fish farm will be easier to manage the water quality and produce a better production. Smart Aquaculture Controlling System is one of the ways to develop the aquaculture industries. Smart Aquaculture Controlling System also known as S-AQUA is basically a system that can control water temperature and pH level of a pond if the water condition is not suitable for the pond. On top of that, aquaculture industry can decrease of human involvement and can save cost as well as time.